Dialectic through the Camera Lens: Hunstanton School - Climent Mondéjar, María José (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
This article aims to address the ability of the architecture to express itself through its own image and the ability of photography to reveal a position in a geopolitical context. All this, understanding by “image” a two-dimensional representation of the architecture and its context, photographed at a specific time. This subject is studied following the example of the Alison and Peter Smithson’s school in Hunstanton, a building that has always been considered, in one way or another, as a “cursed building” by the critics and, for a long time, this tag was also assumed by its authors. The images taken by the Smithsons themselves, as well as those made by their great friend, photographer Nigel Henderson, are containing more complex meanings than those photographs, more static, that have been illustrating known books of History. Through this text the aim is to analyze the interactions between historian and architect, based on the interpretation of the architectural imaginary, in order to conclude what kind of narratives are those that have been used along time to tell an architecture and what are the pretensions that underlie the choice of one type of grammars or others.